Prinsip Kemashalahatan Umat dan Penghargaan Terhadap Hukum Dalam Bingkai Kesadaran Multikultur Kehidupan Beragama di Indonesia - Iskandar, Iskandar (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Indonesia is a country inhabited by various tribes, races and religions. A long history of Indonesian nation with various ethnics make kind of multicultural religious which is brought lives phenomenon. Islam as the majority religion in Indonesia provides significant meaning in appreciating benefit and respecting the diversity religious of people in Indonesia. The concept of rahmatan lil Alamin is seeded according to the context in Indonesia. Thus, an inclusive understanding by collocated Islam as a progressive religion nowadays becomes a necessity to solve problems and the importance of a complex human beneficial. On the other hand, the necessity of multicultural awarenness of religious in Indonesia made this country as barometer of other country in appreciating a fair law to all the citizens, but when the diversity of this nation does not respect other religions, it will bother the religious‟ stability and national life in the country. Islam has given point of views in national life and taught how to respect other people who has different belief. So, people who has different belief should do the same to appreciate Islam. The history of the world has taught us about the importance of appreciate people and respect the law for the nation, then the nation will be a peaceful and prosperous country.